The dynamic mechanical analysis of sugar palm fibre reinforced high impact polystyrene (HIPS) composites - Bachtiar, Dandi; Salit, Mohd Sapuan; Zainudin, Edi Syams; Abdan, Khalina; Mohd Dahlan, Khairul Zaman (2009)
This paper is focuses on the study of the dynamic mechanical properties of short sugar palm fibre reinforced high impact polystyrene (HIPS) composites. The fibre sizes of 30-50 meshes and five different fibre loadings of 10%, 20%, 30%, 40% and 50% by weight have been used. Short SPF-HIPS composites were fabricated using melt mixing and compression moulding. Testing was carried out according the ASTM D5023. The results showed that the addition of short SPF to the pure HIPS increased the storage modulus and thermal stability of the composites.